RESOURCE-EFFICIENCY OF FOUNDRY (UNDER RESULTS OF INTERNATIONAL SCIENTIFIC CONFERENCE «FOUNDRY AND METALLURGY 2010. BELARUS», DEDICATED TO 90-TH ANNIVERSARY OF BYELORUSSIAN NATIONAL TECHNICAL UNIVERSITY) - Ju. N. Fasevich (Литьë и металлургия)
.